IMPROVING THE SPEAKING SKILL OF TENTH GRADE STUDENTS MAJORING IN FASHION THROUGH PODCAST MEDIA AT SMK N 8 SURABAYA - Husna, Nurul (English Language Education Study Program, 2022)
This research aims to find out the students improvement in speaking skills after implementing podcast media in the teaching and learning process. The subject of the research was the tenth-grade students majoring in fashion 2 at SMK Negeri 8 Surabaya in academic 2021 / 2022. Which consisted of 33 students. The method used in this research was Classroom Action Research (CAR) conducted in 2 cycles. Each cycle follows four phases: planning, acting, observing, and reflecting. However, there are different treatment was given in the second cycle. There were two ways of collecting the data were obtained from observation sheet field notes and speaking tests. Based on the data showed significant improvement in their speaking performance after the second cycle was conducted. The target score (KKM) of SMK Negeri 8 Surabaya for English lessons is 70. The result of the research showed that in the pre-cycle only 7 students or 21% of students reached the minimum standard score. In cycle I, 14 students or 42% of students reached the minimum standard score, and in cycle II there were 30 students or 90% of students in X Fashion 2 that could pass the standard minimum score. It could be concluded that the students speaking skills could be improved by using podcasts in teaching and learning speaking.